Association Between Healthy Behaviors and Health Care Resource Use With Subsequent Positive Airway Pressure Therapy Adherence in OSA - Launois, Claire; Bailly, Sebastien; Sabil, Abdelkebir; Goupil, François; Pigeanne, Thierry; Hervé, Carole; Masson, Philippe; Bizieux-Thaminy, Acya; Meslier, Nicole; Kerbrat, Sandrine; Trzepizur, Wojciech; Gagnadoux, Frédéric (Chest, 2024)
The healthy adherer effect has gained increasing attention as a potential source of bias in observational studies examining the association of positive airway pressure (PAP) adherence with health outcomes in OSA. Is adherence to PAP associated with healthy behaviors and health care resource use prior to device prescription? Data from the Institut de Recherche en Santé Respiratoire (IRSR) des Pays de la Loire Sleep Cohort were linked to health administrative data to identify proxies of heathy behaviors, including adherence to cardiovascular (CV) drugs (medical possession ratio), cancer screening tests, influenza vaccination, alcohol and smoking consumption, and drowsiness-related road accidents during the 2 years preceding PAP onset in patients with OSA. Multivariable regression analyses were conducted to evaluate the association of heathy behaviors with subsequent PAP adherence. Health care resource use was evaluated according to subsequent PAP adherence. We included 2,836 patients who had started PAP therapy between 2012 and 2018 (65% of whom were PAP adherent with mean daily use ≥ 4 h/night). Being adherent to CV active drugs (medical possession ratio ≥ 80%) and being a person who does not smoke were associated with a higher likelihood of PAP adherence (OR, 1.43; 95% CI, 1.15-1.77 and OR, 1.37; 95% CI, 1.10-1.71, respectively). Patients with no history of drowsiness-related road accidents were more likely to continue PAP (OR, 1.39; 95% CI, 1.04-1.87). Patients who were PAP adherent used less health care resources 2 years before PAP initiation than patients who were nonadherent (mean number of outpatient consultations: 19.0 vs 17.2, P = .003; hospitalization days: 5.7 vs 5.0; P = .04; ED visits: 30.7% vs 24.0%, P = .0002, respectively). This study indicated that patients who adhere to PAP therapy for OSA were more health-seeking and used less health care resources prior to device initiation than patients who were nonadherent. Until the healthy adherer effect associated with PAP adherence is better understood, caution is warranted when interpreting the association of PAP adherence with CV health outcomes and health care resource use in nonrandomized cohorts.